Occurrence of spontaneous and audiogenic seizures following global brain ischaemia due to cardiac arrest - Ułamek-Kozioł, Marzena; Kocki, Janusz; Bogucka-Kocka, Anna; Januszewski, Sławomir; Czuczwar, Stanisław; Pluta, Ryszard (Folia Neuropathologica, 2015)
Transient cardiac arrest due to cardiac vessel bundle occlusion was used to produce a rat model of spontaneous and audiogenic seizures. Among the rats, spontaneous seizures were present in 64%, and audiogenic seizures could be evoked in 86%, during two weeks of survival after cardiac arrest, by exposure to a loud sound produced by rattling keys, beginning one day after the post-ischaemic injury. Data from literature suggested a key role for GABA-ergic system widespread dysfunction especially in the hippocampus in post-cardiac arrest onset of audiogenic seizures. Reduced GABA inhibition in the hippocampus seems responsible for audiogenic seizures following cardiac arrest. In summary it may be considered that the occurrence of audiogenic seizures following cardiac arrest is determined not only by a neuronal loss, especially in the hippocampus, but also by a condition of synapse modification by a regenerative phenomenon. Data from our study clearly indicate that global brain ischaemia due to cardiac arrest may induce the susceptibility to spontaneous and audiogenic seizures, but this effect is transient.